Determining the Attitudes of Nurses Working in a Private Hospital Group Towards the Employment of Internationally Educated Nurses - Merve Tarhan; Pınar Doğan; Ahu Kürklü (Association of Nurse Managers, 2021)
Aim: This study aimed to determine nurses' attitudes working in a private hospital group towards the employment of internationally educated nurses. Method: The descriptive, cross-sectional study was conducted with 544 nurses working in four private hospitals affiliated with a foundation university in Istanbul. A self-administered questionnaire was used to collect data, including a personal information form, an opinion form on the employment of internationally educated nurses, and the Attitude Scale towards the Employment of Internationally Educated Nurses. Data were analysed using descriptive tests, Mann-Whitney U test, and Kruskal Wallis-H variance analysis. Results: Attitudes towards the employment of internationally educated nurses were low, with a median score of 61.3 (46.2-73.1) out of 125. The attitudes of nurses in the adaptation to the profession and society sub-dimension were lower than the other sub-dimensions with a median score of 20.4 (14.8-25.2). The attitudes towards the employment of internationally educated nurses were significantly lower among nurses with a professional experience of 10 years or more (p=.024), working as managers (p=.019), and being non-supportive about employment (p=.000). Conclusion: The findings indicated that nurses working in a private hospital group were non-supportive of the employment of internationally educated nurses and had negative attitudes, especially in the adaptation to the profession and society. Policymakers, managers, and educators should develop strategies that maximise facilitating the professional and social adaptation of internationally educated nurses and minimise challenging factors for positive working environments.